Photocatalytic degradation of DIPA using bimetallic cu-ni/tio2 photocatalyst under visible light irradiation - Riaz, N. (Hindawi Publishing Corporation, 2014)
Bimetallic Cu-Ni/TiO2 photocatalysts were synthesized using wet impregnation (WI) method with TiO2 (Degussa-P25) as support and calcined at different temperatures (180, 200, and 300°C) for the photodegradation of DIPA under visible light. The photocatalysts were characterized using TGA, FESEM, UV-Vis diffuse reflectance spectroscopy, fourier transform infrared spectroscopy (FTIR) and temperature programmed reduction (TPR). The results from the photodegradation experiments revealed that the Cu-Ni/TiO2 photocatalysts exhibited much higher photocatalytic activities compared to bare TiO2. It was found that photocatalyst calcined at 200°C had the highest photocatalyst activities with highest chemical oxygen demand (COD) removal (86.82). According to the structural and surface analysis, the enhanced photocatalytic activity could be attributed to its strong absorption into the visible region and high metal dispersion. © 2014 Nadia Riaz et al.